PRINCIPLES AND METHODS OF PSYCHOLOGICAL (SPIRITUAL) ANALYSIS IN FICTION LITERATURE (Scientific journal of the Fergana State University, 2023)
Today, various genres, laws related to creative methods, methodological directions, opportunities at different stages of development of literature are widely studied. In Uzbek literature of the 20th century, our writers began to explore new aspects of the human inner world in a transparent and figurative way. Since the main hero of life and literature is a person, it is one of the important tasks that the writer faces in creating a character, expressing his feelings, expressing his attitude to events and objects, expressing his experiences in the inner world of the hero in order to bring him closer to the reader, reflecting his image and siren in different images. The article provides information about the method of psychological analysis, its printouts and methods in the world and Uzbek literature.